Skull base pathology – a diagnostic conundrum. Issue 11 (20th November 2022) - Devakumar, H; Cereceda-Monteoliva, N; Weir, J; Ferguson, M
Abstract: Background: Myoepithelioma is a rare benign neoplasm, most commonly derived from salivary glands, but there are limited cases of extra salivary gland involvement too. There is little knowledge on typical investigative findings and, instead, diagnosis relies on immunohistochemistry analysis. To our knowledge, this paper reports the 13th case of sinonasal myoepithelioma in the English literature. Case report: This paper presents a 25-year-old man who complained of chronic nasal obstruction. A sinonasal mass was noted on examination that appeared benign on imaging. Biopsy revealed a grade 2 chondrosarcoma that was endoscopically resected; however, excisional margins were positive. On histopathological review at the multidisciplinary team meeting, the lesion was more in keeping with chondromyxoid fibroma, but immunohistochemistry analysis confirmed a myoepithelioma lesion. In light of this revised diagnosis, quorate opinion was for follow up with active monitoring. Conclusion: Sinonasal tumours require a thorough history, examination and investigation before a treatment plan can be formulated. If there is diagnostic uncertainty, it is important to keep a wide differential list and seek a second specialist opinion where possible.